Incentives and disincentives of adopting the cool box technology: A field experiment with urban retailers in Moshi, Tanzania - Mwambi, Mercy; Mvungi, Henry; Ernest, Zablon; Termeer, Emma; Dijkxhoorn, Youri (World Vegetable Center, 2024)
Key Findings / Background  Retailers using the cool box technology saved on average USD 3.20 per day per trader while those who did not use lost USD 2.80 per day per trader  The cool box improved the hygiene of vegetables at retail level  Retailers increased the sales volume due to the enhance preservation of fresh vegetables  The technology can be expensive for small retailers and support is required improve affordability